2018
DOI: 10.1016/j.neuron.2017.12.041
|View full text |Cite
|
Sign up to set email alerts
|

TMC Proteins Modulate Egg Laying and Membrane Excitability through a Background Leak Conductance in C. elegans

Abstract: Membrane excitability is a fundamentally important feature for all excitable cells including both neurons and muscle cells. However, the background depolarizing conductances in excitable cells, especially in muscle cells, are not well characterized. Although mutations in transmembrane channel-like (TMC) proteins TMC1 and TMC2 cause deafness and vestibular defects in mammals, their precise action modes are elusive. Here, we discover that both TMC-1 and TMC-2 are required for normal egg laying in C. elegans. Mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 51 publications
8
44
0
Order By: Relevance
“…Recent work also establishes that ecdysozoan Tmc123 paralogs function in body kinesthesia (proprioception), sensory control of locomotion or egg-laying behavior via membrane depolarization, and nociception (Guo et al 2016;Yue et al 2018;Wang et al 2016). In summary, our study further lays the groundwork for understanding the molecular history of a sensory channel family in the context of the evolution of developmental gene regulatory circuits in different animal lineages (Beisel et al 2010;Fritzsch et al 2000;Fritzsch and Elliott 2017;Corbo et al 1997;Cox et al 2018a).…”
Section: Mechanosensation For Animal Body Planssupporting
confidence: 62%
“…Recent work also establishes that ecdysozoan Tmc123 paralogs function in body kinesthesia (proprioception), sensory control of locomotion or egg-laying behavior via membrane depolarization, and nociception (Guo et al 2016;Yue et al 2018;Wang et al 2016). In summary, our study further lays the groundwork for understanding the molecular history of a sensory channel family in the context of the evolution of developmental gene regulatory circuits in different animal lineages (Beisel et al 2010;Fritzsch et al 2000;Fritzsch and Elliott 2017;Corbo et al 1997;Cox et al 2018a).…”
Section: Mechanosensation For Animal Body Planssupporting
confidence: 62%
“…5 Simply speaking, no single molecule has been identified to be associated with all mechanotransduction across phyla such as the ecdysozoan TRP channels also found in bony fish but absent in mammals (BEISEL et al 2010;COX et al 2018b;QIU AND MULLER 2018 (FRITZSCH et al 2006;FRITZSCH et al 2015). Recent work also establishes that ecdysozoan Tmc123 paralogs function in body kinesthesia (proprioception), sensory control of locomotion or egg-laying behavior via membrane depolarization, and nociception (GUO et al 2016;WANG et al 2016;YUE et al 2018). In summary, our study further lays the groundwork for understanding the molecular history of a sensory channel family in the context of the evolution of developmental gene regulatory circuits in different animal lineages (CORBO et al 1997;FRITZSCH et al 2000;BEISEL et al 2010;FRITZSCH AND ELLIOTT 2017;COX et al 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Research by the Garcia Laboratory suggests a developmental function for C. elegans TMC1 with little indication for a role in sensory transduction (Zhang et al 2015), and Wang and colleagues (2016) have demonstrated that TMC1 in worms is critical for alkaline sensation. Intriguingly, Yue et al (2018) linked C. elegans TMC proteins to egg laying and showed that manipulating TMC expression could modulate resting membrane potential via a depolarizing background leak conductance. Furthermore, expression of mammalian TMC1/2 rescued defects in worms deficient for C. elegans TMC proteins (Yue et al 2018).…”
Section: Tmc1/2mentioning
confidence: 99%
“…Intriguingly, Yue et al (2018) linked C. elegans TMC proteins to egg laying and showed that manipulating TMC expression could modulate resting membrane potential via a depolarizing background leak conductance. Furthermore, expression of mammalian TMC1/2 rescued defects in worms deficient for C. elegans TMC proteins (Yue et al 2018). Additional disparate functions have been attributed to the TMC ortholog in Drosophila.…”
Section: Tmc1/2mentioning
confidence: 99%